2022
DOI: 10.3389/fimmu.2022.983621
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant Artemisia vulgaris pollen adjuvanted Art v 1 protein-based vaccine treats allergic rhinitis and bronchial asthma using pre- and co-seasonal ultrashort immunotherapy regimens in sensitized mice

Abstract: Allergic rhinitis is an important risk factor for bronchial asthma. Allergen-specific immunotherapy (ASIT) is the gold standard for treatment of allergic rhinitis, conjunctivitis, and asthma. A disadvantage of current ASIT methods is the length of therapy which requires numerous allergen administrations. The success of ASIT is determined by its schedule, which, depending on the vaccine and type of allergy, can be pre-seasonal (before the allergy season begins), combined pre/co-seasonal (during the allergy seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…All cytokines, except IFN-γ, were upregulated in the AR group. The Rhinocort, DEX, and DEX-Gel groups inhibited the upregulated cytokines to varying degrees, consistent with previous findings [ 45 47 ]. No significant differences in the levels of inflammatory mediator were observed between the Gel and AR groups, indicating that submucosal injections of Gel did not induce additional inflammatory responses.…”
Section: Resultssupporting
confidence: 92%
“…All cytokines, except IFN-γ, were upregulated in the AR group. The Rhinocort, DEX, and DEX-Gel groups inhibited the upregulated cytokines to varying degrees, consistent with previous findings [ 45 47 ]. No significant differences in the levels of inflammatory mediator were observed between the Gel and AR groups, indicating that submucosal injections of Gel did not induce additional inflammatory responses.…”
Section: Resultssupporting
confidence: 92%
“…In a murine model, virus-like nanoparticles with shielded Art v 1 were hypoallergenic and successful in preventive treatment [ 57 ]. A study also showed that the adjuvant is relevant for a successful outcome in allergen-specific immunotherapy in mice [ 58 ]. Food allergies involving defensins have not been investigated in oral immunotherapy protocols.…”
Section: Allergenic Proteins Harboring a Defensin Domainmentioning
confidence: 99%
“…These unmethylated motifs are enriched in microbial DNA, mitochondrial DNA (mtDNA), and fetal DNA; yet these modified sequences are rare in mammalian nuclear DNA (10). Additionally, synthetic CpG oligonucleotides (ODN) are increasingly used in pre-clinical studies and ongoing clinical trials as effective vaccine adjuvants for mucosal vaccines against infectious diseases and allergens (14)(15)(16)(17)(18)(19)(20). However, these studies and trials are devoid in examining the effects of CpG ODN on maternal outcomes during pregnancy.…”
Section: Introductionmentioning
confidence: 99%